Challenges in Implementing Character Education through Scouting Extracurricular Activities in Madrasah Ibtidaiyah - Amik Nadziroh; Nirra Fatmah; Ari Susetiyo (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2026)
Scouting extracurricular activities in Madrasah Ibtidaiyah (MI) play a significant role in fostering students’ character development and discipline. However, their implementation at MI PSM Gempolan II Gurah, Kediri, faces several challenges that hinder the achievement of character education objectives. This study aims to identify and analyze the problems encountered in the implementation of scouting extracurricular activities and to propose appropriate solutions for improvement.This research employs a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. The findings reveal several major issues, including low student motivation, limited number and competence of scout instructors, inadequate facilities and infrastructure, and insufficient parental support. These challenges collectively affect the effectiveness of the program and limit its contribution to students’ character development.Based on these findings, several strategies are recommended, including enhancing instructors’ competence through professional training, improving the availability and quality of facilities, developing more innovative and engaging activity programs, and strengthening communication and collaboration with parents.In conclusion, optimizing these aspects is essential to improve the effectiveness of scouting extracurricular activities, enabling them to contribute more significantly to character building among students at MI PSM Gempolan II Gurah.